Periprocedural management of anticoagulation for atrial fibrillation catheter ablation in direct oral anticoagulant–treated patients. Issue 5 (10th May 2018) - Martin, Anne‐Céline; Lessire, Sarah; Leblanc, Isabelle; Dincq, Anne‐Sophie; Philip, Ivan; Gouin‐Thibault, Isabelle; Godier, Anne
Abstract : Background: Guidelines recommend performing atrial fibrillation (AF) catheter ablation without interruption of a direct oral anticoagulants (DOACs) and to administer unfractionated heparin (UFH) for an activated clotting time (ACT) ≥300 seconds, by analogy with vitamin K antagonist (VKA). Nevertheless, pharmacological differences between DOACs and VKA, especially regarding ACT sensitivity and UFH response, prevent extrapolation from VKA to DOACs. Hypothesis: The level of anticoagulation at the time of the procedure in uninterrupted DOAC–treated patients is unpredictable and would complicate intraprocedural UFH administration and monitoring. Methods: This prospective study included interrupted DOAC–treated patients requiring AF ablation. Preprocedural DOAC concentration ([DOAC]), intraprocedural UFH administration, and ACT values were recorded. A cohort of DOAC‐treated patients requiring flutter catheter ablation was considered to illustrate [DOAC] without DOAC interruption. Results: Forty‐eight patients underwent AF and 14 patients underwent flutter ablation, respectively. In uninterrupted DOAC–treated patients, [DOAC] ranged from ≤30 to 466 ng/mL. When DOAC were interrupted, from 54 to 218 hours, [DOAC] were minimal (maximum: 36 ng/mL), preventing DOAC‐ACT interference. Anyway, ACT values were poorly correlated with UFH doses ( R 2 = 0.2256). Conclusions: Our data showed that uninterrupted DOAC therapy resulted in an unpredictable and highly variable initial level of anticoagulation before catheter ablation. Moreover, even with DOAC interruption preventing interference between DOAC, UFH, and ACT, intraprocedural UFH monitoring was complex. Altogether, our exploratory results call into question the appropriateness of transposing UFH dose protocols, as well as the relevance of ACT monitoring in uninterrupted DOAC–treated patients.